Tourism Development and Local Community Welfare: A Case Study of the Mandalika Special Economic Zone - YULI, Sri Budi Cantika; SEPTIANI, Emilia; PRAMUJA, Risky Angga; SUPIANDI, Supiandi; NAJMUDIN, Mohamad (Journal of Environmental Management and Tourism, 2023)
This study aims to investigate the impact of tourism development on the welfare of local communities in the Mandalika Special Economic Zone (SEZ), Indonesia. Data were collected through semi-structured interviews with key informants, as well as a review of secondary sources. The results indicate that the development of tourism in Mandalika has had a positive impact on the welfare of the local community, specifically in the areas of education, economy, and health. The increase in the number of schools and training programs for entrepreneurship has equipped individuals with the necessary knowledge and skills to become self-sufficient entrepreneurs, which has fostered an entrepreneurial mindset. Additionally, there has been an increase in income and employment opportunities for the local community, with the opening of various types of jobs both informally and formally. Finally, tourism has contributed to improving health facilities such as hospitals, health centers, and clinics. However, this study is limited by the small sample size and the focus on a specific area, which may not be generalizable to other contexts. Future research should explore the impact of tourism development on other aspects of local community welfare and consider the potential negative impacts of tourism development on the environment and cultural heritage.